ATIVIDADE ANTIMICROBIANA DE QUITOSANAS E SEUS DERIVADOS: INFLUÊNCIA DAS CARACTERÍSTICAS ESTRUTURAIS - Macedo,Juliana B. (2022)
In recent years, there has been an increasing interest in the development of antimicrobial materials for different applications, especially in the biomedical field. In this context, chitosan is one of the most employed materials due to its highly attractive properties, such as biocompatibility, biodegradability, non-toxicity, and antimicrobial activity against gram-negative and gram-positive bacteria and fungi. In this review, we discuss the different methods used to obtain chitosan and point out how they affect the structural and chemical properties of this material, followed by a detailed discussion on how these properties influence its antimicrobial activities. Additionally, we summarize the most accepted antimicrobial mechanisms of action for chitosans. Specifically, we aim to provide a comprehensive overview on the last findings and progress reported in the literature on the factors that influence the antimicrobial activity of chitosan, e.g., polymeric average molecular weight ( M W ¯), average degree of acetylation ( D A ¯), water-soluble derivatization and sample degree of purity. The data available in the literature indicate that in addition to the structural properties, the effectiveness of such antimicrobial activity of chitosan is also dependent on the target microorganisms. This review will help researchers to better understand the mechanism of action of chitosan against microorganisms based on its structural characteristics.